Aplicación del gel de alendronato al 1 % como coadyuvante en la terapia periodontal - Franco Iglesias, Cristina Franshesca (2021)
Periodontitis is one of the most common conditions that affect the oral cavity, whose most frequent treatment technique is scraping and root planing. However, according to several studies, this technique is considered insufficient for the treatment of periodontitis, so the application of 1 % alendronate for its effect of inhibiting the production of interleukin-1α (IL), IL-6 and TNF and help new bone formation. Its effect orally shows us an encouraging result of bone regeneration, as shown in this study, but also several studies mentioned in this work show a better result applying it in the form of a 1 % gel and locally as an adjuvant to the mechanical therapy. Conclusion: alendronate 1 %, according to the literature consulted, shows promising results in a local application.